Real‐time manipulation of ZnO nanowires on a flat surface employed for tribological measurements: Experimental methods and modeling. Issue 2 (12th October 2012) - Dorogin, Leonid M.; Vlassov, Sergei; Polyakov, Boris; Antsov, Mikk; Lõhmus, Rünno; Kink, Ilmar; Romanov, Alexey E.
Abstract Elastic and tribological properties of zinc oxide nanowires (NWs) on Si wafer and highly oriented pyrolytic graphite (HOPG) are experimentally investigated and theoretically interpreted. Measurements are performed inside a scanning electron microscope (SEM) using real‐time manipulation technique that enables two possible ways of data registration: "external" force registration with quartz tuning fork (QTF) based sensor and "internal" force registration utilizing in situ observed elastic deformation of NWs. Young modulus is determined by loading half‐suspended NW at its free end and then employed for the following tribological experiments. Maximal static friction force is estimated when NW is being pushed at one end and switches from partial to complete motion upon overcoming static friction. Kinetic friction is extracted from the profile of the NW being uniformly dragged at the midpoint. After being brought to rest after the manipulations, the NW causes redistribution of static friction force from the supporting surface which is calculated and compared with kinetic friction. Thus, it is possible to describe the complete range of tribological phenomena: static friction upon the transition to kinetic friction, pure kinetic friction, and the relaxation of kinetic friction to self‐balanced static friction.